2012
DOI: 10.1371/journal.pone.0035878
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Characterization of Novel Fructosyltransferases and Invertases from Agave tequilana

Abstract: Fructans are the main storage polysaccharides found in Agave species. The synthesis of these complex carbohydrates relies on the activities of specific fructosyltransferase enzymes closely related to the hydrolytic invertases. Analysis of Agave tequilana transcriptome data led to the identification of ESTs encoding putative fructosyltransferases and invertases. Based on sequence alignments and structure/function relationships, two different genes were predicted to encode 1-SST and 6G-FFT type fructosyltransfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 57 publications
1
26
0
1
Order By: Relevance
“…A dendrogram based on an expanded alignment including all available amino acid sequences from experimentally determined members of PGHF32 from dicotyledonous and monocotyledonous species confirmed the classification of the agave sequences (Supplementary Figure 1 ). Previously characterized sequences from A. tequilana (Cortés-Romero et al, 2012 ) are indicated in red.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A dendrogram based on an expanded alignment including all available amino acid sequences from experimentally determined members of PGHF32 from dicotyledonous and monocotyledonous species confirmed the classification of the agave sequences (Supplementary Figure 1 ). Previously characterized sequences from A. tequilana (Cortés-Romero et al, 2012 ) are indicated in red.…”
Section: Resultsmentioning
confidence: 99%
“…RNA extraction and qRT-PCR analysis was carried out as described in Abraham Juárez et al ( 2015 ). Primers used are listed in Cortés-Romero et al ( 2012 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 and 10), suggests that Sucinduced accumulation of FOS observed in stems of this species at 42 DAT (Figs. 2B and 6A) is the result of enzymes other than 1-FFT, such as fructan:fructan 6G-fructosyltransferase (6G-FFT) and sucrose:fructan 6-fructosyltransferase (6-SFT) (Cortés-Romero et al, 2012). This could also be said with regard to the MeJA-Hi treatment in stems.…”
Section: Discussionmentioning
confidence: 99%
“…The first Agave FT to be characterized was a 1-SST from A. tequilana (Avila-Fernandez et al, 2007) and by RNAseq 15 members of PGHF32 from A. tequilana, A. deserti, and A. victoriaereginae were later identified (Avila De Dios et al, 2015). Sequence based predictions of enzyme activities have also been confirmed for some A. tequilana enzymes using the P. pastoris system (Cortes-Romero et al, 2012). cDNAs encoding 6-SFT or 1-FFT type enzymes have not yet been conclusively identified perhaps due to low or tissue specific expression.…”
Section: Agave Fructansmentioning
confidence: 91%